Correlation of Electrocardiogram Derived P Wave Dispersion and Left Ventricular Diastolic Function in Hypertensive Patients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Abnormal PWD expressed the impaired atrial electrical conduction which occurs as a result of structural changes (remodelling) in the atria caused by hypertension )HT). Diastolic function of the left ventricle (LV) have significant role in determination LV filling. Diastolic dysfunction (DD) related with fatality and hospitalization due to heart failure (HF).   Patients and Methods: The study involved 100 individuals with HT. PWD was calculated from 12- leads surface ECG by determining the disparity betwixt the broadest and thinnest P waves. LV mass and left ventricle mass index ( LVMI) and diastolic function measurements were performed.     Results: Correlation studies between PWD and parameters of LV diastolic function (E/A ratio and e`) showed statistically highly significant negative correlation (r = - 0.401, r = - 0.244) subsequently, p,< 0.05). Correlation study of PWD with E/e` showed a positive correlation which was statistically highly significant (r = 0.241, p < 0.05). While the Correlation studies of PWD with left atrial volume (LAV) and left atrial volume index (LAVI) showed statistically no significant positive correlation (r = 0.116, r = 0.029, p,>,0.05). Correlation studies of PWD with LVM and LVMI: showed statistically highly significant positive correlation with (r = 0.474, r = ,0.340respectively, p,